The Occupation of Germany in 1945 and the Politics of German History - Pritchard, Gareth (History compass, 2009)
The invasion and occupation of Germany in 1945 have always been the focus of intense, and highly politicised, academic debate. One reason for this was that both the Federal Republic of Germany and the German Democratic Republic based their claims to legitimacy on their rival interpretations of the significance of 1945. The invasion and occupation of Germany were also central to controversies between the western powers and the Soviets over who was to blame for the outbreak of the Cold War and the division of Germany. Different political factions within the western world held differing views on issues such as the German antifascist committees, denazification, and the expulsion of German populations from eastern Europe. This article examines four important strands within the historiography of 1945 - Communism, anti-Communism, German nationalism, and New Left revisionism - with a particular emphasis on how these strands have been affected by the end of the Cold War and the reunification of Germany. It also explores some exciting new trends in recent scholarship that have few or no precedents in the traditional historiography.